Female general surgeons: current status, perceptions and challenges in South Africa. A pilot study at a single academic complex - Roodt, Liana (Department of Surgery, 2017)
Background: Today, the majority of medical graduates in South Africa and internationally, are female. Current literature suggests that the surgical workforce does not reflect this gender integration. This trend, as well as a decrease in the popularity of general surgery as career choice, has been investigated internationally. It is postulated that gender plays a significant role in specialty choice. In the midst of the gender debate, there are also generational shifts in preferences around work and lifestyle that need to be considered. Paucity of data about these trends from the African continent exists. Aim: The aim of this study was to determine the gender, generational and discipline-specific factors that are currently impacting on general surgery as a career and specialty choice by administering questionnaires to undergraduate students, surgical trainees and consultant surgeons. The questionnaires were designed to determine the: 1. "Status" of female general surgeons as opposed to male general surgeons. 2. "Perceptions" about female general surgeons opposed to male general surgeons. 3. "Challenges" faced by general surgeons, both male and female. Methods: An institutionally validated, self-administered questionnaire was used to gather data on the current status, perceptions and challenges pertaining to general surgeons, male and female, at the University of Cape Town. The questionnaires were distributed to a group of final-year medical students, and to current surgical registrars and surgical consultants in the department of surgery, and were analysed with a particular focus on gender. Results: The response rate from the surgical department was 67.8%: 29 (51%) respondents were consultant surgeons (six female and 23 male), and 28 were surgical registrars (11 female and 17 male). Of the 114 students invited, 59 (51.7%) completed the survey: 18 male and 41 female. Status: The small numbers made it difficult to comment on the status of female surgeons within the discipline. However, the average age of female surgical consultants were six years younger than male consultants (39 vs. 45). Two female consultants were the head of a firm, none has been on the editorial board of a peer-reviewed journal, nor has acted as postgraduate research supervisors, but their average number of publications is almost equivalent to those of the male consultants. Perceptions: A statistically significant proportion of registrars (p = 0.03; six [35%] female and 16 [40%] male) felt that women had an advantage when applying for a surgical training post. A total of 19 (33%) felt that there are too many female surgical registrars; only two (3.5%) felt there are too few. Nine (32%) registrars felt that more female surgeons complicate the departmental routine - male participants were statically more likely to consider a female presence disruptive (p = 0.02). Fourteen (50%) registrars, 13 (45%) consultants and 36 (61%) students think men are better suited for a career in general surgery, but the majority across all groups considers female surgeons just as technically competent as male surgeons. A minority of registrars (5/28: 18%) and consultants (4/29: 13.7%) perceive female surgeons to portray a lot of masculine qualities, while 24 (40.6%) students think female surgeons are more assertive, aggressive and decisive than women in other specialties. Challenges: Poor work-life balance, the effect their surgical career has on their family and personal relationships, together with meeting research and academic demands, were identified as major challenges across both genders in the consultant and registrar groups. The majority of students, both male - 13 (72%), and female - 28 (68%), indicated that perceived lifestyle during training will deter them from choosing a career in general surgery. Nineteen (46.3%) female and six (33%) male students are deterred by the influence a surgical career may have on their personal relationships. Conclusion: This pilot study moves the gender conversation in surgery beyond balancing numbers. More women in surgery does not necessarily translate into better integration - in our survey, men are still considered better suited for a career in general surgery. Women are considered disruptive to the discipline and are perceived to face more challenges in carving out a successful career in general V surgery. There are, however, challenges that increasingly affect both genders. As the number of women in the surgical workforce rise, it will be imperative to distinguish what challenges are discipline rather than gender-related. Addressing gender as well as generational challenges may enable the discipline to draw the best candidates and restore general surgery to its position as a popular career choice.